Investigation of turbulent heat and mass transfer in combustion of the liquid fuel - Askarova, A.S.; Bolegenova, S.A.; Berezovskaya, I.E.; Laptev, V.; Vorobieva, O.D.; Zhanzhienov, A.E.; Iliyeva, M.M.; Karymsakova, L.I. (Recent Contributions to Physics, 2019)
Conducted research of inflammation of the hexadecane depending on the level of pressure in the combustion chamber under given primary conditions. In the process of work, pressure was increased till 200 bars for choosing optimum characteristics of combustion. In the result of work obtained schedules of distribution of the maximum temperature, maximum concentration of the carbon dioxide and water steam, time of inflammation from the pressure in the combustion chamber. Individually provided distribution of the temperature fields at the moment of inflammation and temperature at the moment of active fuel combustion depending on the pressure in the combustion chamber. Based on the obtained results and schedules, chosen optimum pressure equal to 170 bars, when noticed inflammation with the time of delay equal to 0.8 ms, temperature in the combustion chamber is reaching 2697 K, and also discharging relatively low concentration of the carbon dioxide 0.186 g/g.